Educational Model for a Health Promotion Leaflet in Identifying Knowledge and Attitudes toward HIV/AIDS Stigma Prevention in the Community - Imas Yoyoh; Elang Wibisana; Rita Sekarsari (Yayasan Daarul Huda Kruengmane, 2026)
HIV/AIDS remains a significant global and national public health challenge, not only from a clinical perspective but also in its social implications. Persistent stigma toward people living with HIV/AIDS (PLWHA) continues to hinder early detection, treatment adherence, and social integration. Limited public health literacy contributes to misconceptions about HIV transmission and reinforces social discrimination. The Brief Health Promotion leaflet model represents a concise educational approach that delivers contextual and easily understandable health information. This community service initiative aimed to identify the level of knowledge and attitudes toward HIV-related stigma prevention among residents of Tangerang City using a Brief Health Promotion leaflet strategy. The activity was conducted at Benteng Stadium through leaflet distribution combined with brief interpersonal education. The findings indicated that public knowledge was generally high; however, attitudes toward stigma prevention remained at a moderate level. This educational model appears effective as an initial strategy to enhance HIV literacy, yet sustained and comprehensive educational approaches are required to strengthen stigma prevention efforts within the community.